1997
DOI: 10.1002/(sici)1097-0134(199704)27:4<493::aid-prot3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

High resolution fast quantitative docking using fourier domain correlation techniques

Abstract: A 'docking' method based on finite grid forcefield sampling is proposed for fast evaluation of interaction energies between macromolecules and ligands. Forcefield used to calculate interaction energies utilizes a potential energy function composed of a 1/r-dependent electrostatic term and a (6-12) Lennard-Jones term for van der Waals interactions. Fast evaluation makes use of the convolu-tion theorem allowing a point-by-point N-dimensional correlation in direct space to be replaced by a simple multiplication i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…We can note that there is a correlation only for the low value of HINT (<0.8) or for the high value of vdW (>−0.2). The differences between vdW and HINT potentials (as mentioned above, HINT has also a vdW component) can be explained in terms of the different distance dependence of these potentials with respect to electrostatic interactions 26. The vdW potential has a distance dependence notably different and becomes predominant in intermolecular complexes27 when electrostatic interactions are not determinant.…”
Section: Discussionmentioning
confidence: 97%
“…We can note that there is a correlation only for the low value of HINT (<0.8) or for the high value of vdW (>−0.2). The differences between vdW and HINT potentials (as mentioned above, HINT has also a vdW component) can be explained in terms of the different distance dependence of these potentials with respect to electrostatic interactions 26. The vdW potential has a distance dependence notably different and becomes predominant in intermolecular complexes27 when electrostatic interactions are not determinant.…”
Section: Discussionmentioning
confidence: 97%
“…Our tests indicate that reducing the grid interval from 1.05 to 0.8 Å extends the range of distinction between NCMs and decoys by 100 Å 2 but it does not improve the statistical significance of the NCMs. Docking of small ligands to proteins using different grid intervals (0.25-2 Å ) showed that only very high-resolution grid representations (<0.4 Å ) produced good predictions (Blom and Sygusch, 1997). Working with such high resolutions is currently unrealistic in protein-protein docking because of the memory load and computation time.…”
Section: Discussionmentioning
confidence: 99%
“…The docking of a particular molecule or certain molecules in a particular conformation or more than one conformation is performed to identify the ligands. The evaluation of the various docking procedures has shown that they are able to find the docking results that are similar to the experimental structures (Blom & Sygusch, 1997;Ewing & Kuntz, 1997;Jones, Willett, Glen, Leach, & Taylor, 1997;Morris, Goodsell, Huey, & Olson, 1996). To identify the proteins that are related to certain side effects, the data from the medical biochemistry literature (Baynes & Dominiczak, 2009) were utilized.…”
Section: Literature Surveymentioning
confidence: 99%